LOCAL AND TARGET CULTURE MATERIALS: INSIGHT INTO TEACHERS’ PERSPECTIVES - Chris Asanti; Syamdianita Syamdianita (Universitas Islam Sumatera Utara (UISU), 2018)
In this contemporary world, English is used to link the communication among people internationally for different universal purposes (Crystal, 2003; Jenkins, 2010; and Kirkpatrick, 2011), for instance, educational advancement, career development, technology, and international relation. It is obvious that the function of English during this period of time has made some countries generate policies to include English as one of the compulsory subjects being taught at schools. However, the materials which are used in school practices are likely to focus on the target culture materials. Due to this reason, it seems that the role of local and target cultures in teaching the language should be taken into consideration. Related to the status of English to the importance of culture in language learning, this research aims at investigating English teachers’ perspectives on the appropriateness of materials in English Language Teaching. In order to get broader pictures, questionnaires and interview were conducted to two English teachers in Samarinda. The results were interesting as both teachers preferred to expand the materials rather than used the readily materials provided by the school and/or the institution. This created them to become material developers and creators. Other results showed that the teachers were aware of the importance of the cultural content in the materials, thus culture functioned as ‘a filer and a connecting bridge’ in ELT.